Hyponatremia in Tuberculosis Meningitis: Navigating the Diagnostic Challenges of Cerebral Salt Wasting – A Case Report - Yousra Nasir Siddiqui (Journal of Bahria University Medical and Dental College)
A 10 year old female presented with fever, headache and vomiting since four days. Her laboratory workup revealed low serum sodium, serum osmolality. CT scan of the brain was unremarkable, while on CSF examination, protein, and total leukocyte count (predominantly lymphocytes) were increased. CSF cultures were negative, however, GeneXpert detected rifampicin resistant mycobacterium tuberculosis. Due to her high urine output and hyponatremia with sodium of 128 mEq/l, fluid restriction was attempted in order to rule out the diagnosis of SIADH, but the patient was unresponsive to it. Thus, the patient was diagnosed with tuberculous meningitis after further workup, followed by cerebral salt wasting. She was started on anti-tuberculous therapy (ATT), 3% hypertonic saline and flucrocortisone, to which she was responsive, and eventually discharged.